Dimensi-dimensi Komunikasi Efektif dalam Relasi Bimbingan dan Konseling - Suherman Suherman (Indonesian Journal of Educational Counseling, 2019)
DIMENSIONS OF EFFECTIVE COMMUNICATION IN GUIDANCE AND COUNSELING RELATIONS. The growth of effective communication between guidance and counseling teachers and students is a facility to achieve the goal of guidance and counseling in schools. Quality of communication will psychologically stimulate students to involve themselves intensively in the process of providing treatment. This condition will encourage students to open themselves to understand the personal characteristics, and willing to work together to explore various alternatives for self-development, making choices and decisions, and solving their problems. Students who are less open to guidance and counseling teachers are motivated by various factors, including allegedly by low professional competence of guidance and counseling teachers in developing communication that facilitates the provision of assistance for students. Thus, guidance and counseling teachers need to have communication competence in order to improve the effectiveness of aid in guidance and counseling services. The dimensions of the communication shall include: (a) the empathic behavior; (b) the acceptance and respect of students; (c) the warmth and attention; (d) openness and sincerity; and (e) concreteness and specificity of expression.